Inter- and intra-farm land fragmentation in Viet Nam - Thomas Markussen; Finn Tarp; Do Huy Thiep; Nguyen Do Anh Tuan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper uses panel data at commune, household, and plot levels to study the causes and effects of agricultural land fragmentation in rural Viet Nam. We focus on both inter-farm fragmentation (the division of land into many small farms) and intra-farm fragmentation (the division of each farm into many small plots). In both these dimensions, land holdings in Viet Nam are highly fragmented. Results show strong effects of both inter- and intra-farm fragmentation on labour input per hectare in agriculture. When productivity is measured by profits per hectare, we estimate a positive effect of farm size on productivity. Results on the determinants of fragmentation show that land sales markets reduce inter-farm fragmentation in the south of Viet Nam but not in the north. Administrative land consolidation programmes have some positive impact on land consolidation in the north but not in the south.
Keywords: 330; land fragmentation; consolidation; farm size; productivity; land markets; Viet Nam